Elicitive Curricular Development A Manual for Scholar-Practitioners Developing Courses in International Peace and Conflict Studies - Echavarría Alvarez, Josefina (innsbruck university press, 2019)
The Elicitive Curricular Development Manual (ECDM) is a systematic collection of experiences and lessons identified in academic contexts around the world in Austria, Cambodia, Colombia, Brazil, Ethiopia and Iraq. The ECDM reflects core elicitive principles such as the importance of a focus on relationships, looking beyond the episode of conflict, collaboration, communication and local knowledge. These principles are consistent with the mission of the Research Center for Peace and Conflict (InnPeace) to teach, learn and research as reflective processes of relevant social questions of peace and conflict transformation. This manual offers helpful guidelines for academic and administrative staff, as well as international cooperation partners trusted with developing peace and conflict courses at the graduate and postgraduate levels. - Das "Elicitive Curricular Development Manual" basiert auf einer systematischen Sammlung von Erfahrungen und Erkenntnissen zur Entwicklung von Studiengängen in der Friedens- und Konfliktforschung in Äthiopien, Brasilien, Irak, Österreich, Kambodscha und Kolumbien. Der im Handbuch dargelegte Zugang zur Curricular-Entwicklung beschreibt die Zentralität von Beziehungen und die Notwendigkeit Konfliktanalyse über deren Episode hinaus auszudehnen als zentrale Prinzipien. Dabei stehen Zusammenarbeit, Kommunikation und die systematische Einbeziehung von lokalem Wissen im Zentrum der Bemühungen. Dieses Buch bietet Orientierung für die internationale Entwicklung von Curricula in der Friedens- und Konfliktforschung.